Configuring Cisco AVVID : Architecture for Voice, Video, and Integrated Data - Lawson, Wayne (Syngress Publishing, Inc., 2011)
What is AVVID? Previously called Configuring Cisco Communications Networks (CCN), Architecture for Voice, Video, and Integrated Data (AVVID) is the latest development from Cisco Systems that will soon redefine the way businesses communicate. AVVID allows businesses to transmit voice, data, and video over one combined architecture, whereas in the past, three separate systems were required. Configuring Cisco AVVID will be the first book to discuss the components of the AVVID architecture and will be timed to release with the launch of the technology in early 2000.